2013
DOI: 10.3389/fphar.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subpopulations of prairie voles differentially susceptible to peer influence to decrease high alcohol intake

Abstract: Peer influences are critical in the decrease of alcohol (ethanol) abuse and maintenance of abstinence. We previously developed an animal model of inhibitory peer influences on ethanol drinking using prairie voles and here sought to understand whether this influential behavior was due to specific changes in drinking patterns and to variation in a microsatellite sequence in the regulatory region of the vasopressin receptor 1a gene (avpr1a). Adult prairie voles’ drinking patterns were monitored in a lickometer ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Combined with the above data, this finding indicates that Ucn1 cells were activated in response to alcohol, particularly in male voles. To test the hypothesis that alcohol decreases anxiety-like behaviors in prairie voles as has been demonstrated for other animals, we tested the effect of an injection of a low dose of alcohol (1.06 g/kg), comparable to what is consumed in a drinking bout (16,18), on anxiety-like behavior in the elevated plus maze (EPM). As expected, the alcohol-treated voles spent more time in the open arms [t(13) = 2.02, P = 0.032] and less time in the closed arms [t(13) = 1.87, P = 0.042]; accordingly, they had a greater proportion of time in the open arms [t(13) = 1.97, P = 0.035] than did saline-treated subjects.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Combined with the above data, this finding indicates that Ucn1 cells were activated in response to alcohol, particularly in male voles. To test the hypothesis that alcohol decreases anxiety-like behaviors in prairie voles as has been demonstrated for other animals, we tested the effect of an injection of a low dose of alcohol (1.06 g/kg), comparable to what is consumed in a drinking bout (16,18), on anxiety-like behavior in the elevated plus maze (EPM). As expected, the alcohol-treated voles spent more time in the open arms [t(13) = 2.02, P = 0.032] and less time in the closed arms [t(13) = 1.87, P = 0.042]; accordingly, they had a greater proportion of time in the open arms [t(13) = 1.97, P = 0.035] than did saline-treated subjects.…”
Section: Significancementioning
confidence: 99%
“…In both species, social reward and drug reward show striking parallels at the behavioral and neurobiological levels (5-9). Prairie voles are now being used to explore the interactions between social relationships and drug abuse (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).We previously demonstrated that prairie voles voluntarily selfadminister substantial amounts of alcohol (ethanol) and can influence the drinking patterns of a social partner (16)(17)(18)(19), similar to social drinking in humans (20). Because alcohol is known to influence social bonds in humans (21-24), we asked here whether alcohol consumption can affect the formation of adult social attachments in prairie voles.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to better understand the processes by which peer influences take effect in prairie voles, Anacker and Ryabinin (2013) measure alcohol intake during periods of isolation, pair housing of high and low drinkers, and subsequent isolation. By using a new method ("lickometer" apparatus) and cross-correlation analyses, they managed to differentiate subpopulations of high drinkers that were and were not responsive to social influence to decrease ethanol intake.…”
mentioning
confidence: 99%